The Crimson Fairy Book - Lang, Andrew, 1844-1912 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Crimson Fairy Book" by Andrew Lang is a collection of fairy tales edited by the well-known folklorist during the late 19th century. This anthology features a diverse array of stories drawn from various cultures, including Hungarian, Russian, and Servian tales, which have been adapted for young audiences. The overarching theme revolves around magical adventures, trials, and the timeless battle between good and evil, often highlighting the cunning of heroes and the downfalls of deceivers. At the start of "The Crimson Fairy Book," the editor provides a preface that outlines the purpose of the collection and addresses the origins of the stories, which have been passed down through oral tradition over many centuries. The opening story, "Lovely Ilonka," introduces a prince who embarks on a quest to find three magical bulrushes that ultimately lead him to a beautiful maiden. However, his plans go awry when a deceitful swineherd's daughter is mistaken for his beloved, setting off a series of events that highlight themes of love, betrayal, and ultimately, redemption. This narrative exemplifies the blend of adventure and moral lessons found throughout the collection, engaging readers with fairy tale magic. (This is an automatically generated summary.)
Lovely Ilonka -- Lucky Luck -- The Hairy Man -- To your Good Health! -- The Story of the Seven Simons -- The Language of Beasts -- The Boy who could keep a Secret -- The Prince and the Dragon -- Little Wildrose -- Tiidu the Piper -- Paperarello -- The Gifts of the Magician -- The Strong Prince -- The Treasure Seeker -- The Cottager and his Cat -- The Prince who would seek Immortality -- The Stone-cutter -- The Gold-bearded Man -- Tritill, Litill, and the Birds -- The Three Robes -- The Six Hungry Beasts -- How the Beggar Boy turned into Count Piro -- The Rogue and the Herdsman -- Eisenkopf -- The Death of Abu Nowas and of his Wife -- Motikatika -- Niels and the Giants -- Shepherd Paul -- How the wicked Tanuki was punished -- The Crab and the Monkey -- The Horse Gullfaxi and the Sword Gunnfoder -- The Story of the Sham Prince, or the Ambitious Tailor -- The Colony of Cats -- How to find out a True Friend -- Clever Maria -- The Magic Kettle.
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Stonecutter
Release date is 2000-12-01
J.C. Byers and David Widger
Keywords: Fairy tales; Folklore